2017
DOI: 10.1002/stem.2583
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Postnatal Human Epidermal Keratinocytes Toward Functional Neural Crest Fates

Abstract: During development, neural crest cells are induced by signaling events at the neural plate border of all vertebrate embryos. Initially arising within the central nervous system, neural crest cells subsequently undergo an epithelial to mesenchymal transition to migrate into the periphery, where they differentiate into diverse cell types. Here we provide evidence that postnatal human epidermal keratinocytes, in response to FGF2 and IGF1 signals, can be reprogrammed toward a neural crest fate. Genome-wide transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 40 publications
2
39
0
Order By: Relevance
“…Primarily, non-NC cells (fibroblasts, keratinocytes, etc.) are isolated in vitro (Figure 4b) (V. K. Bajpai et al, 2017).…”
Section: | Signaling Events Regulating Nc Inductionmentioning
confidence: 99%
“…Primarily, non-NC cells (fibroblasts, keratinocytes, etc.) are isolated in vitro (Figure 4b) (V. K. Bajpai et al, 2017).…”
Section: | Signaling Events Regulating Nc Inductionmentioning
confidence: 99%
“…Recently, in our laboratory, Bajpai et al devised a method to reprogram postnatal human epidermal keratinocytes (KCs) to NClSC (termed KC‐NC) by mimicking signaling events that occur at the neural plate border. Transcriptomic analysis confirmed that epidermally derived NCISCs were similar to those generated from human embryonic stem cells (ESCs) and maintained the multilineage differentiation potential into melanocytes, neurons, SC, and mesenchymal cells in vitro and in ovo . In a subsequent study, we identified the factors that promote expansion of KC‐NC and maintain the NC phenotype.…”
Section: Sources Of Nc‐like Stem Cells In Adult Tissuesmentioning
confidence: 71%
“…Recently, our laboratory showed that cultures of KC from interfollicular epidermis could be the source of NClSCs (termed KC‐NC), after induction with specific chemical cues . KC‐derived NCISCs could be coaxed to differentiate into functional neurons, SC, melanocytes, osteocytes, chondrocytes, adipocytes, and smooth muscle cells in vitro.…”
Section: Ncscs: a Cell Source For The Treatment Of Demyelinating Disomentioning
confidence: 99%
“…Therefore, cultures of human NC cells can provide a model to study human disease and a source of stem cells for treatment of neurodegenerative diseases that may be currently hindered by the lack of an easily accessible and autologous cell source. Interestingly, recent studies have successfully isolated NC cells from different tissues in the adult body, including the adult hair follicle, craniofacial sources such as the palate and the oral mucosa . Recently, our laboratory showed that NC could be derived from cultures of epidermal KCs isolated from glabrous neonatal foreskin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our laboratory showed that NC could be derived from cultures of epidermal KCs isolated from glabrous neonatal foreskin. KC‐derived NC could be coaxed to differentiate into functional neurons, Schwann cells, melanocytes, osteocytes, chondrocytes, adipocytes and smooth muscle cells, in vitro and in vivo, in lineage tracing experiments in chick embryos . Given the accessibility of human skin, KC‐derived NC may provide a valuable source of multipotent stem cells for treatment of myelopathies and other debilitating neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%